Validation of Environmental Chemistry LKM Based on The Mangrove Ecosystem to Pre-Service Students' - Saija, Maryone; Tahya, Dominggus; Filindity, Yuli Tamar (Jambura Journal of Educational Chemistry, 2024)
This study aims to produce a worksheet enriched with the mangrove ecosystem to improve pre-service students' critical thinking skills under a valid category. The research method executes by R&D with the focus outlined in the validation of student worksheets based on mangrove ecosystems. The instruments were a validation sheet filed by 4 experts in chemistry and education and a questionnaire. Validation is carried out through discussion with the research team about the feedback and suggestions to correct the improvements and direct improvements in assessing LKM. This research found that the LKM based on the mangrove ecosystems was valid, readability, and ready to use in field trial learning.